Sincerity Transforms Workplace Approval Seeking Behavior Driven By Nafs Ammarah Dominance: Keikhlasan Mentransformasi Perilaku Mencari Pengakuan Kerja Akibat Dominasi Nafs Ammarah - Nikmah Rochmawati; Azzah Nahdiyya Armina (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The digital era intensifies external validation dependency in professional environments. Specific Background This reliance on social recognition creates psychological exhaustion and unstable work motivation among employees. Knowledge Gap Current motivation theories often overlook spiritual dimensions, leaving a void in understanding and mitigating validation dependency within Islamic professional contexts. Aims This study analyzes the psychological roots of external validation dependency through the nafs concept and proposes sincerity as a transformative motivation model. Results The findings reveal that nafs ammarah dominance drives employees to rely on external judgments, leading to severe burnout. Conversely, sincerity provides a stable motivational foundation centered on transcendental meaning rather than fleeting social appraisal. Novelty This research formulates a unique behavioral transformation framework based on tazkiyatun nafs, integrating the stages of takhalli, tahalli, and tajalli. Implications Integrating these spiritual practices broadens Islamic work psychology discourse and offers practical applications for counseling and human resource development programs. Highlights Employees depending on external validation face severe psychological exhaustion and unstable professional drive. Cultivating ikhlas creates stable intrinsic motivation centered on transcendental meaning rather than social appraisal. Integrating tazkiyatun nafs stages provides a practical framework for mitigating digital era validation dependency. Keywords Nafs Ammarah; Sincerity; Approval Seeking Behavior; Islamic Psychology; Work Motivation